Multi-hierarchical Framework – Fuzzy Entropy Weight Approach for Auditing Technology in PT X - Achmad Danu Firdaus; Udisubakti Ciptomulyono (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2018)
PT X is an Indonesia leading company in ship repair field. With the growth of shipyard industries in Indonesia, company is expected to compete within tight competition. Problems arise when the reparation processes can’t be finished on schedule. Respect to high vessel repairing demands, it can be a serious problem for company as they have many of ships waiting to be repaired. Management of technology might be the first step to solve the problem. Repair process within company is supported due to good management of technology policies. That’s why technology assessment is necessary in this company. This research is proposed to be used as recommendation to PT X on how to measure and assess the technological capabilities of company. Technology Audit Model (TAM) is used as basic technology assessment model. While multi-hierarchical framework - Fuzzy Entropy Weight Approach (FEWA) are tools used to process the multi-criteria of assessment model. Based on the assessment, it can be known the weight and rank of all criteria, by which are be utilized as input for SWOT analysis. Based on this process, the the improvement strategies could be generated. The proposed strategies are knowledge sharing program, environmental impact evaluation, and project network.